Science and education: modern trends - Zakharova A. N., Girenko L. A., Yusupova L. G., Kosianchuk N. M., Chernykh A. V., Prosvetova T. S., Kosheleva A. O., Shevchenko O. I., Tsvetkova A. L., Kozelkova E. N., Vasikova A. F., Bobrovskii D. N., Bekulov K. M., Tkhazeplova M. K., Bekulova I. B., Polikarpova L. A., Khandramai A. A., Kochevadov V. A., Evseeva L. A., Nesterova L. V., Bugaeva M. A., Bugaev S. V., Zhuravliova O. V., Valuev O. S., Bokova O. A., Shamarina E. V., Bobrikov V. N., Bazhin K. S., Ravochkin N. N., Masiukova L. V., Ponomariova N. A., Tereshko Z. A., Garkusha N. S., Chebarykova S. V., Evteeva N. V. (Science and education: modern trends, 2015)
the following research deals with investigation results on developing of students' readiness to intracultural communication. The authors analyzed and defined the streams of foreign language training among students. Diagnostics of components and statistic analyses of data on development of readiness to intracultural communication of non-linguistic faculties students was performed.
Keywords: межкультурная коммуникация; иностранный язык; толерантность; эмпатия; поликультурная среда; multicultural environment; tolerance; foreign language; empathy; intracultural communication